Interior of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The mandapa (pillared hall) of the Suhaveshwar Temple is of a square design, with lateral transepts to the north and south sides. The pillars are along the exterior dwarf walls of the mandapa that support the circular dome ceiling. The mandapa does not have any pillars in the centre of the mandapa, making it an astylar variety mandapa.